PERSEPSI SISWA SMAN 9 PEKANBARU TERHADAP PENGGUNAAN MEDIA FLASHCARD DIGITAL DAN FLASHCARD KERTAS DALAM PENGUASAAN KOSAKATA BAHASA JEPANG - Arif, Mario Fauzan; Basri, Merri Silvia; Yohani, Adisthi Martha (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study analyzes students' perceptions of the use of digital flashcardmedia and paper flashcard in mastering Japanese vocabulary. The purpose of this study was to find out whether there are differences in students' perceptions at SMAN 9 Pekanbaru towards the use of digital flashcard media and paper flashcard in mastering Japanese vocabulary. This study uses a quantitative descriptive analysis method with 27 respondents of class XI IPA 4 SMAN 9 Pekanbaru. Data were obtained through a Likert-based closed questionnaire and analyzed using descriptive statistics. The results of the study showed that overall students' perceptions of digital flashcard were in the positive category while students' perceptions of paper flashcard were in the moderate category. This study concludes that students' perceptions state that the use of digital flashcard media and paper flashcard in helping to master Japanese vocabulary is a fairly good choice and has a good impact on helping students' mastery of Japanese vocabulary, although both digital flashcard media and paper flashcard media have their own advantages and disadvantages.Keywords: Perception, Vocabulary, Japanese, Flashcard, SMAN 9 Pekanbaru